2012
DOI: 10.1371/journal.ppat.1003038
|View full text |Cite
|
Sign up to set email alerts
|

HCMV-Infected Cells Maintain Efficient Nucleotide Excision Repair of the Viral Genome while Abrogating Repair of the Host Genome

Abstract: Many viruses subvert the host cell's ability to mount and complete various DNA damage responses (DDRs) after infection. HCMV infection of permissive fibroblasts activates host DDRs at the time of viral deposition and during replication, but the DDRs remain uncompleted without arrest or apoptosis. We believe this was in part due to partitioning of the damage response and double strand break repair components. After extraction of soluble proteins, the localization of these components fell into three groups: spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 76 publications
(96 reference statements)
2
29
0
Order By: Relevance
“…To provide areas in the nucleus for replication compartments to develop, the compaction and movement of chromatin is observed (O'Dowd et al, 2012; Strang et al, 2012b Several facets of HCMV replication compartment organization and function late in infection have recently been described, each involving the localization of HCMV protein UL44. UL44 is the putative processivity subunit of the HCMV DNA polymerase (Ertl & Powell, 1992), and several different phosphorylated forms of UL44 are present in the infected cell (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide areas in the nucleus for replication compartments to develop, the compaction and movement of chromatin is observed (O'Dowd et al, 2012; Strang et al, 2012b Several facets of HCMV replication compartment organization and function late in infection have recently been described, each involving the localization of HCMV protein UL44. UL44 is the putative processivity subunit of the HCMV DNA polymerase (Ertl & Powell, 1992), and several different phosphorylated forms of UL44 are present in the infected cell (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the full repertoire of viral and cellular proteins acting in concert during DNA synthesis has yet to be described. These proteins probably include those viral and cellular proteins that associate with UL44 and/or UL84 (Gao et al, 2008;Strang et al, 2009Strang et al, , 2010a, several proteins that have illdefined roles in viral DNA synthesis (for example, UL36, IRS1 and IE2; Sarisky & Hayward, 1996), plus viral and cellular proteins involved in DNA damage responses and viral DNA repair O'Dowd et al, 2012;. How these and other proteins are organized within HCMV replication compartments is unclear but may involve UL44.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fibroblasts, large bipolar viral replication centers (RCs) are formed within 48 h postinfection (hpi) and certain host cellular proteins become strongly associated with these RCs (1; reviewed in reference 2). These proteins include the regulatory protein p53 (3), as well as numerous components of the host cellular DNA damage response (DDR) and repair pathways (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Some viruses appear to require DDR proteins for efficient replication (10,11), while for other viruses an efficient DDR can be detrimental to their DNA replication (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Studies from several labs, including our own, have shown that HCMV infection initiates the ataxia telangiectasia mutated (ATM)-dependent double-strand break (DSB) DDR (4)(5)(6)(7)(8). ATM is a key sensing protein involved in initiating DSB repair, as well as cellular growth and differentiation (22).…”
mentioning
confidence: 99%